Prevalence of childhood overweight and obesity and associated factors in Peru - Emma C. Preston; Proochista Ariana; Mary E. Penny; Melanie Frost; Emma Plugge (Revista Panamericana de Salud Pública)
OBJECTIVE:To determine the prevalence of and factors associated with childhood overweight and obesity among a cohort of children 7-8 years of age in Peru. METHODS: This was a cross-sectional secondary analysis of data from the Young Lives longitudinal study of childhood poverty. The sample was a cohort of 1 737 children 7-8 years of age in 2009. Prevalence of overweight and obesity was assessed using body mass index-forage Z-scores. Logistic regression was used to determine associations with a number of individual, household, and community factors. RESULTS: Prevalences of overweight and obesity were 19.2% and 8.6%, respectively. A prevalence of 32.0% and 23.5% overweight and obesity was found among males and females, respectively. High socioeconomic status, living in Lima, having a mother who was overweight or obese, being male, and being an only child or having only one sibling were associated with being overweight and obese at this age. CONCLUSIONS: This study shows a high prevalence of childhood and maternal overweight and obesity in Peru. In contrast to findings in many high-income countries, the findings in Peru indicate that children from wealthier households were more likely to be overweight or obese than those from poorer households. In addition, there is something particularly obesogenic about the Lima environment that merits further investigation, and several key issues to consider when targeting future interventions and research.